Intracranial Compliance Concepts and Assessment: A Scoping Review - Ocamoto, Gabriela Nagai; Russo, Thiago Luiz; Mendes Zambetta, Rafaella; Frigieri, Gustavo; Hayashi, Cintya Yukie; Brasil, Sérgio; Rabelo, Nicollas Nunes; Spavieri Júnior, Deusdedit Lineu (Frontiers in Neurology, 2021)
Background: Intracranial compliance (ICC) has been studied to complement the interpretation of intracranial pressure (ICP) in neurocritical care and help predict brain function deterioration. It has been reported that ICC is related to maintaining ICP stability despite changes in intracranial volume. However, this has not been properly translated to clinical practice. Therefore, the main objective of this scoping review was to map the key concepts of ICC in the literature. This review also aimed to characterize the relationship between ICC and ICP and systematically describe the outcomes used to assess ICC using both invasive and non-invasive measurement methods. Methods: This review included the following: (1) population: animal and humans, (2) concept of compliance or its inverse “elastance,” and (3) context: neurocritical care. Therefore, literature searches without a time frame were conducted on several databases using a combination of keywords and descriptors. Results and Discussion: 43,339 articles were identified, and 297 studies fulfilled the inclusion criteria after the selection process. One hundred and five studies defined ICC. The concept was organized into three main components: physiological definition, clinical interpretation, and localization of the phenomena. Most of the studies reported the concept of compliance related to variations in volume and pressure or its inverse (elastance), primarily in the intracranial compartment. In addition, terms like “accommodation,” “compensation,” “reserve capacity,” and “buffering ability” were used to describe the clinical interpretation. The second part of this review describes the techniques (invasive and non-invasive) and outcomes used to measure ICC. A total of 297 studies were included. The most common method used was invasive, representing 57–88% of the studies. The most commonly assessed variables were related to ICP, especially the absolute values or pulse amplitude. ICP waveforms should be better explored, along with the potential of non-invasive methods once the different aspects of ICC can be measured. Conclusion: ICC monitoring could be considered a complementary resource for ICP monitoring and clinical examination. The combination and validation of invasive/non-invasive or non-invasive measurement methods are required.